1983
DOI: 10.3109/00016348309155791
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial foam Cells

Abstract: Four patients with endometrial foam cells are described. In one the endometrium was obtained after parturition. It showed decidua and endometritis, whereas in the second patient, who had received birth control medication in the past, the endometrium was proliferative. In both cases there was a considerable amount of endometrial hemorrhage. The foam cells in these two patients had little granularity, and their cytoplasm contained hemosiderin. The other two patients received exogenous estrogen and presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Many of the reported cases were associated with endometrial carcinoma [3–5]; in our case obstruction may have occurred because of post-menopausal cervical stenosis, as no evidence of malignancy was found on histopathology sections. Barua et al [6] proposed infection ( E. coli or P. vulgaris ) as a cause of XGE.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Many of the reported cases were associated with endometrial carcinoma [3–5]; in our case obstruction may have occurred because of post-menopausal cervical stenosis, as no evidence of malignancy was found on histopathology sections. Barua et al [6] proposed infection ( E. coli or P. vulgaris ) as a cause of XGE.…”
Section: Discussionmentioning
confidence: 61%
“…The first case of XGE was described by Barua et al [6] in 1978. Subsequent authors have added a few cases (Table 1): Buckley and Fox [7] in 1980 (2 cases), Ashkenazy et al [5] in 1983 (4 cases), and Pounder and Iyer [3] in 1985 (1 case). Blanco et al [8] in 1989 (1 case), Russack and Lammers [4] in 1990 (6 cases), Rivas and Phillipe [9] in 1996 (2 cases), and Kim and Lee [10] in 2002 described cases of nodular histocytic hyperplasia, which is considered to be a variant of XGE.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, only a small number of cases of xanthogranulomatous inflammation occurring in female genital tract have been described, most frequently affecting the endometrium and sometimes associated with endometrial carcinoma [1–3]. In 1978, Barua et al described the first case of XGE without evidence of endometrial carcinoma or hyperplasia [4].…”
Section: Discussionmentioning
confidence: 99%
“…In 1983, Ashkenazy et al described four cases with endometrial foamy cells. Two of their cases were presented with endometrial hyperplasia or carcinoma and the other two isolated XGE cases revealed hemosiderin in foamy cells [3]. In 1985, Pounder and Iyer reported a case of XGE associated with endometrial adenocarcinoma [1].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, endometrial hyperplasia and endometrial carcinomas have been detected in patients with XGI with endometritis [14]. Therefore, cytological and histological diagnosis is important to rule out endometrial cancer in XGI cases.…”
Section: Discussionmentioning
confidence: 99%